Seven Things I Wish I’d Known About Derby - Wallach, Hanna (DerbyLife, 2013)
Recently, I did a lot of thinking about some things I never expected to learn when I started playing roller derby. It took me a long time to work these things out – arguably longer than it probably should have done! – so in an effort to shortcut some of this process for others, I’ve put together the following list (in no particular order) of Things I Learned. This list is a work in progress, but even in its current form, I think it may well be useful, especially to fresh meat.